Durability of a heat-reflective coating on an asphalt pavement. Issue 11 (2nd November 2022) - Yi, Yong; Jiang, Yingjun; Fan, Jiangtao; Zhang, Yu; Deng, Changqing; Tian, Tian; Ji, Xiaoping
Abstract : A heat-reflective coating can be used to solve various problems, including rutting and deformation caused by the excessively high asphalt pavement temperatures during summer. However, the durability of the heat-reflective coatings applied to asphalt pavement has not been extensively researched. The colour changes, crack development and attenuation of the cooling performance are studied along with the changes in skid resistance and cooling performance because of wear. Subsequently, the lifespan of the heat-reflective coating is predicted based on the results. This study indicates that the amount of spraying is positively correlated with the cooling performance. After 120 days of aging, a B–A type coating shows no cracks or any decay in performance. When the wear rate is less than 40%, the skid resistance of the coating meets the required specifications and the coating exhibits good cooling performance. The lifespan of the heat-reflective coating is predicted to be one year.